Postmortem changes in the meat quality of Amazonian fish of the species (Piaractus brachypomus, Arapaima gigas, Brycon amazonicus, Pseudoplatystoma punctifer, Colossoma macropomum. Bibliographic review. - Enriquez Estrella, Miguel Angel (Revista Colombiana de Investigaciones Agroindustriales, 2022)
This work is based on a bibliographic review in which the postmortem changes of 5 species of Amazonian fish (Piaractus brachypomus, Arapaima gigas, Brycon amazonicus, Pseudoplatystoma punctifer, Colossoma macropomum) and how these influence the quality of the The objective of this work has focused on those articles that present information on the physical, chemical and microbiological changes that occur in meat and some existing conservation methods, a total of 33 articles have been selected, of which 18 are in English, 5 in Portuguese and 10. The results obtained highlight the importance of the cold in the conservation of the species, as well as the management of modified atmospheres that regulate the degradation that is generated by the postmortem change, in conclusion, the slaughter , handling and preservation have a great effect on the quality of the product.